Code Share : 5 Continents, 10 Biennales, 20 Artists. - Huldisch, Henriette; Papastergiadis, Nikos; Rees, Simon; Rindzeviciuté, Eglé; Siuolaikinio meno centras, Vilnius Contemporary Art Centre, Vilnius (Vilnius : Contemporary Art Centre, 2009)
Arceneaux, Edgar ; Aguilizan, Alfredo & Isabel ; Bamadhaj, Nadiah ; Brannon, Matthew ; Buckingham, Matthew ; Yu Cheng-Ta ; Dodge, Harry ; Kahn, Stanya ; Eriksson, Annika ; Gladwell, Shaun ; Wong Hoy-Cheong ; Hüner, Emre ; Just, Jesper ; Lee, Jane ; Lyall, Scott ; Miksys, Darius ; Noiritu, Grace ; Ong, Sherman ; Rohde, Kate ; Saadeh, Raeda ; Ugochukwu, Bright
biog. per kunstenaar
Bendrasis Kodas : 5 Zemynai, 10 Bienaliu, 20 Menininku, Siuolaikinio meno centras, Vilnius, 2009 sausio 16 - kovo 8
Code Share : 5 Continents, 10 Biennales, 20 Artists, Contemporary Art Centre, Vilnius, January 16 - 8 March, 2009
boek